At Home and Abroad: U.S. Labor Market Performance in International Perspective - Osberg, Lars (Relations Industrielles / Industrial Relations, 2003)
Reviews the book "At Home and Abroad: U.S. Labor Market Performance in International Perspective," by Francine D. Blau and Lawrence M. Kahn.
Keywords: AT Home & Abroad: US Labor Market Performance in International Perspective (Book); BLAU, Francine D.; BOOKS -- Reviews; KAHN, Lawrence M.; LABOR market; Nonfiction